Pengaruh Perkebunan Inti Rakyat (PIR) terhadap Pendapatan Petani Desa Seraras Kecamatan Sekadau Hilir Kabupaten Sekadau - Kristianus Heri Hartanto (Pusat Penelitian dan Pengabdian kepada Masyarakat, 2023)
This study aims to determine the PIR management system, and the income of oil palm PIR farmers. The research was conducted in Seraras Village, Sekadau District, Sekadau District, West Kalimantan Province, in June-July 2015. The method used in this research is descriptive analysis method, which is a research method based on solving actual problems that exist today. There are 2 samples taken, namely landowners, landowners working alone in their own land. The type of data taken is Snowball Sampling, with an interview and documentation system. The results of this study indicate that there are 2 PIR processing systems, namely, land owners who employ employees, and self-employed owners who work on their own land. The income of land owner farmers who employ employees is Rp. 22,208,215 years/ha, and the income of farmers working on their own land is IDR 20,828,178 years/ha. Keywords: PIR, Income, Farmers, Plasma, Sekadau